Application of control samples in the determination of cigarette safety indicators - N. P. Samoylenko; I. G. Kandashkina; E. Y. Smirnova (Новые технологии, 2017)
To ensure cigarette safety the components of tobacco smoke - nicotine, tar and carbon monoxide are monitored. When determining the content of these substances, the correctness and stability of analytical processes are of great importance, which is ensured by the use of control samples. A project of interstate standard on the requirements for the control sample and its application, which is necessary for testing cigarettes, as well as for carrying out inter-laboratory comparative tests has been developed.